Controlling the Filling and Capping Operation of a Bottling Plant using PLC and SCADA - Kunal Chakraborty; Indranil Roy; Palash De; Soubhik Das (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
This paper presents basic stages of operation of a bottling plant, i.e. the filling and capping process. The main aim of our paper is to control the filling and capping section of a bottling plant simultaneously. At first a set of empty bottle is run by using a conveyer towards filling section, after the operation, the filled bottles are sent towards the capping section. After successful capping operation, the sealed bottles terminate towards exit and a new set of empty bottle arrive, in this way the process continues. This paper includes the method using which, a bunch of bottles can be filled and capped at one instant of time. This method has made the operation more flexible and time saving. The filling and capping operations are controlled using Programmable Logic Controllers (PLC), as the PLC’s are very much user-efficient, cost-effective and easy to control. By using PLC automation the whole process is kept under control. SCADA (Supervisory Control and Data Acquisition) is used to monitor the process by means of a display system.